Holistic shipwreck assemblages in 14th and 15th century southeast Asia - Fahy, B (2015)
The ceramic trade throughout Medieval Southeast Asia was prolific. Terrestrial sites have yielded massive amounts of ceramic material and the archaeological reports of shipwreck cargoes corroborate the versatile and extensive qualities of trade ceramics in the region. The sheer quantity of ceramic artefacts found in shipwreck assemblages, paired with a well-researched framework of the aesthetic, demonstrates that we rely heavily on ceramic data to date wrecks and establish regional trading patterns. While ceramics typically represent the bulk of the recovered material in these instances, many other types of material are present in the various assemblages. Yet these "lesser" materials suffer from a lack of investigation and, therefore, play virtually no role in the archaeological and historical assessment of the ship, its cargo, and its relationship to the maritime economy of the period. While ceramic studies may provide a general overview, a consideration of the other material provides subtlety and nuance to the analysis. This case study focuses on the non-ceramic assemblages for six shipwrecks from the 14th and 15th Centuries of Southeast Asia (three Chinese-built and three Southeast Asian-styled junks). The typological study of the metallurgical, organic and geological material from these wrecks can complement much of the work surrounding existing trade models as well as reveal new concepts of crew life, belief systems and culture. These facets come together to offer a more holistic narrative as well as stimulating the need within the region for more study regarding the locations where past peoples mined and manufactured raw metals. The thesis will also consider the motivations behind the excavators of these projects and what role this plays in the interpretation of the non-ceramic material. One wreck was excavated by treasure hunters, one was done by an amateur archaeologist and a curator, and a third was excavated by a governmental organization. Two excavations were conducted by a non-profit foundation in conjunction with a National Museum and a final one was a purely academic excavation. Each party brings their own experiences and motivations to the excavation and therefore the systems of collection, curation, and conservation weigh heavily and are varied. These factors can determine what priorities each excavator brings to the analysis of excavated objects and the extent to which this effects the subsequent interpretation of the shipwreck.